Experiencing Intercultural Communication an Introduction - Judith N. Martin, Thomas K. Nakayama (McGraw-Hill, 2005)
This popular introduction text covers the core concepts of intercultural communication and offers an experience-based, skill building framework that can be used for everyday communication across cultures.